CONTEXTUAL REALISM: Feminist Epistemology ‘Out of the Fly Bottle’? - Karuvelil, George (2016)
Feminist epistemology, like other epistemologies that are built on the debris of modern epistemology, is strong in its critique of the infirmities of modern epistemology but weak in delivering objective knowledge. Since the heart of feminist epistemology is the situatedness of the knower, it needs to attain objectivity or universality of truth without compromising on diversity and subjectivity. Although the problem is not unique to the feminists, it is more pressing for them because unlike some shades of postmodernism that do away with all universal norms, feminists are committed to the Enlightenment ideals of justice, freedom, and emancipation, all of which call for objectivity and universality beyond one’s preferred group. Faced with this situation, the present paper outlines an epistemological position dubbed as contextual realism. As a form of realism, it makes room for objectivity and its contextualism for subjectivity and diversity.
Keywords: Evidence; Feminist Epistemology; Objectivity; Quine; Situatedness; Wittgenstein